Prognostic evaluation and choice of second-line treatment for patients with advanced non-small-cell lung cancer. (June 2012) - Di Maio, Massimo; Morabito, Alessandro; Daniele, Gennaro; Giordano, Pasqualina; Piccirillo, Maria Carmela; Costanzo, Raffaele; Sandomenico, Claudia; Montanino, Agnese; Gridelli, Cesare; Rocco, Gaetano; Perrone, Francesco
SUMMARY  Patients with progressive disease after first-line treatment for advanced non-small-cell lung cancer have a limited life expectancy. In the second-line setting, a better understanding of prognostic factors and the availability of a prognostic score can contribute to a sensible evaluation of the risks and benefits associated with treatment. We previously showed that the prognosis of patients receiving second-line treatment is significantly conditioned by gender, performance status, histology, stage, previous platinum use and response to first-line treatment. A prognostic score based on these factors allows for the classification of patients into three categories. The score is simple to calculate because all of the variables considered are routinely collected as part of the baseline clinical evaluation of patients. For the majority of non-small-cell lung cancer patients, in the absence of known molecular predictive factors, the choice of second-line treatment among drugs with demonstrated efficacy should necessarily take into account prognosis and the risk:benefit ratio of patients.